On The Investıgatıon Of Medıa Dıscourse - Imanova, Nahida Mahmud (Advances in Social Sciences Research Journal, 2017)
The article deals with the investigation of media discourse. It states that there are two view points according to the determination of the media discourse. According to the first approach the media discourse is a specific type of speech act, and it is observed only in the branch of mass media information. According to the next approach the discourse which is observed in any process of mass media can be meant as media discourse. This viewpoint can be called correct as each discourse which is used in mass media is considered to be media discourse. One of the scientists investigating the notion of discourse N.Fairclough writes: “.... the content of the information may be given before analyzing the form because the content of the information is realized in some form. Form is a part of a content.” (Fairclough 1989, p.108). The realization of mass media, especially the media discourse is used through the means of the computer and the internet. One ways of communication is media discourse. Media discourse serves some certain purposes of the activity of mass media subjects.